Characterization of treatment and outcomes in a population-based cohort of patients with chronic lymphocytic leukemia referred for cytogenetic testing in British Columbia, Canada. (April 2017) - Huang, Steven J.; Lee, Lauren J.; Gerrie, Alina S.; Gillan, Tanya L.; Bruyere, Helene; Hrynchak, Monica; Smith, Adam C.; Karsan, Aly; Ramadan, Khaled M.; Jayasundara, Kavisha S.; Toze, Cynthia L.
Highlights: Patients who required therapy had 4.7 times greater risk of death vs. the untreated. Front-line fludarabine therapy lead to longer time-to-next-treatment vs. alkylator. No difference in overall survival with fludarabine or alkylator front-line therapy. Median time from initial treatment to relapse therapy was 1.9 years. Abstract: This study evaluates outcomes in chronic lymphocytic leukemia (CLL) based on first-line therapy in a large consecutive population-based cohort of 669 patients with fluorescence in-situ hybridization (FISH) data in British Columbia, Canada during the period when chemoimmunotherapy was standard first-line treatment. When analyzed as a time-dependent variable, patients who required treatment (n = 336) had a 4.7 times higher hazard of death than patients who did not (95% confidence interval 2.8–7.9, P < 0.001). The majority of patients received fludarabine-rituximab (FR) in front-line. On multivariate Cox regression analysis, fludarabine-based first-line therapy predicted longer time-to-next-treatment (TTNT) (HR 0.53, 95% confidence interval 0.33–0.87, P = 0.012) but no difference in overall survival (OS) compared to alkylator-based therapy. Deletion 17p was an independent predictor of worse TTNT and OS. The most common second-line treatments were cyclophosphamide-vincristine-prednisone-rituximab and FR. There was no difference in OS between patients retreated in second-line with the same first-line regimen (n = 33) versus different regimen (n = 113). In conclusion, front-line treatment with fludarabine leads to a longer time until need for next treatment than alkylator-based therapy; however, fludarabine or alkylator therapy produces no difference in OS. This study provides a historical baseline for the comparison of novel agents with standard treatments in CLL on a population-level.